2021
DOI: 10.1111/ppc.12971
|View full text |Cite
|
Sign up to set email alerts
|

Determining the relationship between health anxiety and healthy lifestyle behaviors, and the factors that affect them: A cross‐sectional study in Turkey

Abstract: Purpose This study was conducted to determine the relationship between health anxiety (HA) and healthy lifestyle behaviors (HLBs), and the factors that affect them. Design and Methods This descriptive, cross‐sectional, and relational study was conducted with 1007 voluntary participants between June 1 and September 30, 2020. Findings The participants' mean age was 33.46 ± 15.42 years. A positive‐significant relationship was found between the participants' total HA and HLBs scores (r = 0.06, p = 0.03). The simpl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…This finding implies that individuals who experience higher levels regard exercise as a strategy to cope with their anxiety. A study that found an association between health anxiety and the desire to exercise that adds some credence to this viewpoint (Gülhan et al, 2021 ). In addition, a cross-sectional study determined that health anxiety increases the tendency toward healthy lifestyle behaviors such as exercise, good nutrition, and positive interpersonal relationships.…”
Section: Introductionmentioning
confidence: 97%
“…This finding implies that individuals who experience higher levels regard exercise as a strategy to cope with their anxiety. A study that found an association between health anxiety and the desire to exercise that adds some credence to this viewpoint (Gülhan et al, 2021 ). In addition, a cross-sectional study determined that health anxiety increases the tendency toward healthy lifestyle behaviors such as exercise, good nutrition, and positive interpersonal relationships.…”
Section: Introductionmentioning
confidence: 97%